Large-Scale and Mesoscale Distribution of Plankton Biomass and Metabolic Activity in the Northeastern Central Atalntic - Hernández-León, Santiago; Gómez, May; Aristegui, J.; Montero del Pino, María F.; Torres Curbelo, Santiago; Almeida Peña, Carlos; Kühner, Eugen; Brenning, Ullrich; Hagen, Eberhard (2018)
Plankton biomass and indices of metabolism and growth [electron transport system (ETS), glutamate dehydrogenase (GDH) and aspartate transcarbamylase (ATC) activities] were studied over a 2,800 km east-west section of the tropical North Atlantic Ocean (21°N) in <200, 200–500 and >;500 µm size classes. On the large-scale, zooplankton (>;200 µm) enzymatic activities increased westward in the study section, where large cyanobacteria chains (Trichodesmium spp.) were observed. Parallel to it, an increase in medium calanoids (1–2 mm length) was observed towards the western part of the transect, whereas small calanoids (<1 mm) were dominant throughout the boundary area of the subtropical gyre. Microplankton ETS and mesoplankton ETS and ATC activities seemed to match the wave length of low frequency waves. Our results suggest that such waves are related to the observed enhancement of metabolic activity of micro- and mesoplankton. The large-scale and mesoscale variability observed give evidence of the inadequacy of assuming a steady-state picture of the euphotic zone of tropical and subtropical waters.